Carnap's Transformation of Epistemology and the Development of His Metaphilosophy. (6th October 2018) - Uebel, Thomas
Abstract: Carnap's lectures at the 1935 Paris Congress for the Unity of Science marked the beginning of his mature metaphilosophy. This paper considers what role remained for epistemology once it was "purified" of all psychological elements as Carnap there demanded. It is argued that while this did mean the end of traditional epistemology, room was found for nontraditional versions in the course of the further development of Carnap's logic of science.